Combined treatment of melatonin and sodium tanshinone IIA sulfonate reduced the neurological and cardiovascular toxicity induced by deltamethrin in zebrafish. (March 2020) - Li, Meng; Zhang, Ti; Jia, YiQing; Sun, YuMeng; Zhang, ShaoZhi; Mi, Ping; Feng, ZeYang; Zhao, Xin; Chen, DongYan; Feng, XiZeng
Abstract: The pyrethroid insecticide deltamethrin has been reported to have an effect on vertebrate development and cardiovascular disease. Sodium tanshinone IIA sulfonate (STS) is considered to have cardioprotective effects and melatonin is known to regulate sleep-waking cycles. In this experiment, we used transgenic zebrafish Tg (kdrl:mCherry) and Tg (myl7:GFP) to investigate whether STS and melatonin could reverse the cardiovascular toxicity and neurotoxicity induced by deltamethrin. Zebrafish embryos were exposed to 25 μg/L deltamethrin at 10 hpf and treated with 100 mmol/L STS and 1 μmol/L melatonin showed that deltamethrin treatment affected normal cardiovascular development. In situ hybridization and qRT-PCR results showed that deltamethrin could interfere with the normal expression of cardiovascular development-related genes vegfr2, shh, gata4, nkx2.5, causing functional defects in the cardiovascular system. In addition, deltamethrin could affect the sleep-waking behavior of larvae, increasing the activity of larvae, decreasing the rest behavior and the expression of hcrt, hcrtr, aanat2 were down-regulated. The addition of melatonin and STS can significantly alleviate cardiovascular toxicity and sleep-waking induced by deltamethrin, while restoring the expression of related genes to normal levels. Our study demonstrates the role of STS and melatonin in protecting cardiovascular and sleep-waking behavior caused by deltamethrin. Highlights: Cardiovascular and neuroprotective effects of STS and MT on zebrafish larvae. DM causes heart and vessel morphology and functional damage, affecting sleep-waking. Heart beat amplitude to evaluate cardiac function and angiogenesis simulation. Affect the expression of vegfr2, shh, gata4, nkx2.5 and hcrt, hcrtr, aanat2.